(NmIR BALETA(B. s (NiSTORIQ(B, (NTWOR^ESTWO(B, (NWOSPOMINANIQ(B.s - (NnINA tIMOFEEWAs ((NmOSKWAs (NtERRAs, 1993)
(NkNIGA IZWESTNOJ BALERINY nINA tIMOFEEWOJ POSWQ]ENA ISKUSSTWU HOREOGRAFIIs
(NkNIGAs
Keywords: (NISKUSSTWAs